Development of the recombinant fimbrial protein F17 of Escherichia coli and the immune response in alpaca peripheral blood mononuclear cells (PBMC) - Siuce M., Juan (2021)
Escherichia coli is associated with diarrhoea that can cause death in young alpacas. Patotypes of E. coli use the fimbriae to adhere to the host in the first stage of pathogenesis. Therefore, the present study aimed to develop and produce a recombinant protein of E. coli fimbrial adhesin F17 and to evaluate its immunogenicity in alpaca peripheral blood mononuclear cells (PBMC). BL21 was used as an expression vector, the recombinant protein was purified by immobilized affinity chromatography and the production of PBMC cytokines was evaluated 48 and 72 hours after the challenge with F17. The results indicate a significant increase in the production of Th1/Th2 cytokines, predominantly IFN-γ and IL-4. Therefore, the BL21-F17 mixture could be considered as a potential vaccine candidate for the prevention of diarrhoea in alpacas produced by E. coli.